Brain–computer interface in an inter-individual approach using spatial coherence: Identification of better channels and tests repetition using auditory selective attention. (May 2023) - de Souza, Ana Paula; Soares, Quenaz B.; Mendes, Eduardo M.A.M.; Felix, Leonardo B.
Abstract: Auditory Brain–Computer Interfaces (BCIs) have been studied with the main purpose of improving the quality of life of totally paralyzed people. BCIs based on Auditory Selective Attention (ASA) may have distinct features, such as the number of sound sources and most approaches presented in literature use individualized settings. This setup requires more training of individuals or adjustments of the internal classifiers. In this context, a generalized approach can be an interesting alternative for an interface tailored to application and without the need for exhaustive training. The present work investigates ASA using stimuli with AM modulation and spatial coherence to evaluate its value in the modulating frequency and the electrodes position. The objective is to identify better combinations of electrodes and evaluate the number of repetitions and the intervals between them in an inter-individual approach. The best result obtained using the modular classifier, proposed in an earlier work, reached average hit rates of 75% and information transfer rate (ITR) of 2.217 bits/min, considering three windows (5.1 s). This result was obtained using AM stimuli (500 Hz and 2 kHz carriers) and a combination of mostly frontal and prefrontal electrodes and considering 5 s interval between repetitions. With these results, an implementation of a vision-free BCI that covers inter-individual differences could allow users to communicate through selective auditory attention without previous training of subjects. Highlights: Spatial Coherence (SP) is useful in the detection of Auditory Selective Attention for inter-individual BCI. Electrode setup and interval between stimuli must be identified. Frontal and prefrontal electrodes and 5s interval between repetitions showed best results. Proposed electrode setup may be used in offline mode without retesting.